PENGEMBANGAN MODUL PELATIHAN PENULISAN KARYA ILMIAH BERBASIS ANDRAGOGI BERBANTUAN CMS MOODLE - giarti, sri (Kelola: Jurnal Manajemen Pendidikan, 2016)
The objectives of these  research are to develop the steps of the module,  to knowing  the validity of the module, and to find out how high the level of training results using the training module  based on the andragogy and CMS Moodle. To achieve these objectives the researcher using R & D research whithin two stages, i.e. preliminary studies and development of the module. In preliminary studies conduct a review of the literature about development of training module, Moodle and andragogy, and survey to get a existing training modules. In the development of the module there is develop of draft module to be validated by  the experts, and limited field testing. The limited field testing included 7 elementary teachers. The research instrument using test and CAR proposal rubric. The data analysis using descriptive categories and Man Whitney U test. The results are: 1) the steps of the training using the module are: analysis, design, development, implementation, and evaluation; 2) the validity level of the module is in a good category; and 3) the training using the CAR module based on the basic of andragogy with CMS Moodle is higher than before.